Growth of Thalamocortical Fibers to the Somatosensory Cortex in the Human Fetal Brain - Krsnik, Željka; Majić, Visnja; Vasung, Lana; Huang, Hao; Kostović, Ivica (Frontiers in Neuroscience, 2017)
Thalamocortical (TH-C) fiber growth begins during the embryonic period and is completed by the third trimester of gestation in humans. Here we determined the timing and trajectories of somatosensory TH-C fibers in the developing human brain. We analyzed the periods of TH-C fiber outgrowth, path-finding, “waiting” in the subplate (SP), target selection, and ingrowth in the cortical plate (CP) using histological sections from post-mortem fetal brain [from 7 to 34 postconceptional weeks (PCW)] that were processed with acetylcholinesterase (AChE) histochemistry and immunohistochemical methods. Images were compared with post mortem diffusion tensor imaging (DTI)-based fiber tractography (code No NO1-HD-4-3368). The results showed TH-C axon outgrowth occurs as early as 7.5 PCW in the ventrolateral part of the thalamic anlage. Between 8 and 9.5 PCW, TH-C axons form massive bundles that traverse the diencephalic-telencephalic boundary. From 9.5 to 11 PCW, thalamocortical axons pass the periventricular area at the pallial-subpallial boundary and enter intermediate zone in radiating fashion. Between 12 and 14 PCW, the TH-C axons, aligned along the fibers from the basal forebrain, continue to grow for a short distance within the deep intermediate zone and enter the deep CP, parallel with SP expansion. Between 14 and 18 PCW, the TH-C interdigitate with callosal fibers, running shortly in the sagittal stratum and spreading through the deep SP (“waiting” phase). From 19 to 22 PCW, TH-C axons accumulate in the superficial SP below the somatosensory cortical area; this occurs 2 weeks earlier than in the frontal and occipital cortices. Between 23 and 24 PCW, AChE-reactive TH-C axons penetrate the CP concomitantly with its initial lamination. Between 25 and 34 PCW, AChE reactivity of the CP exhibits an uneven pattern suggestive of vertical banding, showing a basic 6-layer pattern. In conclusion, human thalamocortical axons show prolonged growth (4 months), and somatosensory fibers precede the ingrowth of fibers destined for frontal and occipital areas. The major features of growing TH-C somatosensory fiber trajectories are fan-like radiation, short runs in the sagittal strata, and interdigitation with the callosal system. These results support our hypothesis that TH-C axons are early factors in SP and CP morphogenesis and synaptogenesis and may regulate cortical somatosensory system maturation.